Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3329/jemc.v1i2.11465
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Dermatological Cases Attending Skin-VD Outpatient Department in a Medical College Hospital of Bangladesh

Abstract: Background: The pattern of skin diseases varies from one country to another and even from region to region of the same country. We are geographically placed in the tropical region with natural outcome of communicable diseases. We conducted this cross sectional study in a tertiary hospital of Bangladesh keeping the proposition in mind that infectious diseases occupy maximum percentage among skin and venereal diseases in outpatients in Bangladesh.Objectives: To classify the diseases attending the Skin & VD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 2 publications
3
5
1
Order By: Relevance
“…In 1995, Bahmadan et al [22] There are several studies conducted in Bangladesh had found different results than ours. According to them, the prevalence was higher is rural areas [15], among students [10], patients from low socio-economic status [9], among illiterate patients [9,10], in rainy season [8]. According to Khanum et al 52.16% of the patients with low socio-economic status showed a high reoccurrence of skin disease which contradicts our study result [8].…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…In 1995, Bahmadan et al [22] There are several studies conducted in Bangladesh had found different results than ours. According to them, the prevalence was higher is rural areas [15], among students [10], patients from low socio-economic status [9], among illiterate patients [9,10], in rainy season [8]. According to Khanum et al 52.16% of the patients with low socio-economic status showed a high reoccurrence of skin disease which contradicts our study result [8].…”
Section: Resultscontrasting
confidence: 57%
“…Approximately, 40% of people live in urban cities and the highest 10.3 million people live in Dhaka city [7]. Several papers have studied common skin and venereal diseases in Bangladesh [8][9][10][11][12][13][14] but our paper is specifically concerned about fungal skin diseases and their associated factors in three tertiary care hospitals of an urban city, Dhaka, Bangladesh.…”
Section: Tinea Versicolorismentioning
confidence: 99%
“…But a profile of skin diseases was done in children of Saurashtra in India 6 , which revealed 8.5% were eczema cases. Another study 13 in Enam Medical College revealed 23.42% eczema cases among the patients attending Skin VD OPD. But in this study it was high in 40-49 years, probably due to the higher proportion of diabetic patients in that age group.…”
Section: Resultsmentioning
confidence: 95%
“…12 Another study conducted on skin and sexually transmitted diseases at Enam Medical Collage Hospital (2009-10) revealed that in 12100 patients the percentage of eczema was 23.42%. 13 Eczema is one of the most important skin diseases which cause the public health problem. 14 Though it causes negligible mortality but most of the cases of eczema have chronic course and sufferings.…”
Section: Introductionmentioning
confidence: 99%
“…Disease pattern of a given population is generally determined by different ecological and other factors [2]. Customs, habits, religious beliefs, languages, climate are not so varied in different parts in this country, but socio-economic conditions and ignorance play vital role for various presentations of dermatological condition [3]. In a subtropical, just landing in a lower middle income economic country like Bangladesh, poverty, illiteracy, lack of awareness, unhygienic condition along with pollutions from of rapid industrialization have their effects increasing the burden of skin diseases [4].…”
Section: Introductionmentioning
confidence: 99%